Cancer treatment in pregnant women - Basta, Pawel; Bak, Anna; Roszkowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 2015)
In general, strategies for the treatment of cancer in pregnancy should not differ significantly from the treatment regimens in non-pregnant women. However, this is difficult due to either the effects of anticancer drugs on the developing foetus or the possibility of long-term complications after the exposure to drugs and radiation. The decision about the introduction and continuation of treatment in the event of pregnancy should be preceded by a detailed analysis of the potential benefits and risks. There are no data to suggest that pregnancy termination alters the biological behaviour of the tumour or patient prognosis in the presence of appropriate antineoplastic therapy. All patients should be given appropriate advice and informed that there are insufficient scientific data to determine any generally accepted consensus. It is very important to always respect the will of the patient, and the moral judgment of the physician should have no impact on the decisions taken by the woman. If the woman decides to undergo active treatment and maintain her pregnancy, it is necessary to carry out consultations with experts in the field appropriate to the type of cancer. This paper presents a basic review of the literature on the targeted therapies currently used in selected cancers diagnosed during pregnancy: breast cancer, cervical cancer, Hodgkin’s disease, melanoma, thyroid cancer, ovarian cancer, and colorectal cancer.